Differences in Health-Related Physical Fitness and Academic School Performance in Male Middle-School Students in Qatar: A Preliminary Study - Hermassi, Souhail; Hayes, Lawrence D.; Sanal-Hayes, Nilihan E. M.; Schwesig, René (Frontiers in Psychology, 2022)
This study examined differences in the level of physical fitness and academic performance between male middle school children based on different body status categories. Sixty-nine males (age: 12.4 ± 0.7 years of age; body mass: 58.5 ± 7.2 kg; height: 1.62 ± 0.09 m; body mass index (BMI): 22.4 ± 3.3 kg/m2) participated and were divided into BMI age-adjusted groups (i.e., lowest, middle, and highest BMI). Height, mass, BMI, Stork test of static balance, 10 and 15 m sprint as indicator for speed, hand-grip strength test; agility T-half test, medicine ball throw (MBT), the Yo-Yo Intermittent Recovery Test level 1 (Yo-Yo IR1) were assessed. School records were retrieved for grade point averages (GPA) of Mathematics, Science and Arabic. We found significant group differences regarding anthropometric (height: p2 = 0.24, mass: p2 = 0.33, BMI: p2 = 0.66) physical (sprint 10 m: p2 = 0.26) and academic (mathematics: p2 = 0.19, science: p2 = 0.15) performance parameters. The largest difference (p < 0.001) was observed between the lowest and highest group for 10 m sprint. All pairwise differences were between lowest and highest BMI group or the lowest and middle BMI group. No relevant (r > 0.5) correlation between parameters of different dimensions (e.g., anthropometric vs. physical performance parameters) was found. In conclusion, the highest BMI group exhibited similar physical and academic performances than the lowest group. Thus, these data emphasize the importance and appropriate to engage young Qatari schoolchildren in physical activity as it associates with superior academic performance.